A Study of Phytoplankton Distribution in Al-Kabir Al-Shamali River Connected with Nutrients (NO3-- NO2-- NH4+-PO4---) Concentration Changes - جورج ديب; نديم حمود (Latakia University Journal -Biological Sciences Series, 2023)
This study was carried out during the period 2011–2010 for 12 months. 110 species of phytoplankton in Al-Kabir Al-Shamali River were identified including 4 species of Euglenophyta, 15 species of Cyanophyta, 49 species of Chrysophyta, 40 species of Chlorophyta and 2 species of Pyrrophyta. Some physicochemical parameters of water were determined. Some of them were the temperature which ranged between 10.8–28°C, the pH 7.76–8.2 and the BOD 1.6–10mg/l, while the concentrations of NO3- ranged between 1.10-250 mg/l, nitrate 0.13-0.01mg/l, and PO4- ions 0.015–1.05 mg/l. The highest value of ammonium ions was 6.25mg/l and the lowest was 0.011 mg/l. BOD concentrations ranged between 6.06-12.07mg/l.